Structure Properties, Acquisition Protocols, and Biological Activities of Oleuropein Aglycone - Xu, Fangxue; Li, Yujuan; Zheng, Mengmeng; Xi, Xiaozhi; Zhang, Xuelan; Han, Chunchao (Frontiers in Chemistry, 2018)
Oleuropein aglycone, which is the major phenolic component of extra virgin olive oil, is gaining popularity and importance in scientific and public communities. This paper summarizes the structure properties, acquisition protocols, and biological activities of oleuropein aglycone. There are three hydrolytic methods used to obtain oleuropein aglycone from oleuropein-enzymatic hydrolysis, acid hydrolysis, and acetal hydrolysis. Enzymatic hydrolysis can be achieved with exogenous enzymes and endogenous enzymes. In addition, the diverse pharmacological effects of oleuropein aglycone are summaried. These pharmacological effects include anti-Alzheimer's disease, anti-breast cancer, anti-inflammatory, anti-hyperglycemic, anti-oxidative, and lipid-lowering properties. Therefore, we can use hydrolysis and biological activities to study oleuropein aglycone in the future.